Paracrine signaling in mammary gland development: what can we learn about intratumoral heterogeneity? - Rosen, Jeffrey M (BioMed Central, 2014)
Paracrine signaling mechanisms play a critical role in both normal mammary gland development and breast cancer. Dissection of these mechanisms using genetically engineered mouse models has provided significant insight into our understanding of the mechanisms that guide intratumoral heterogeneity. In the following perspective, we briefly review some of the emerging concepts in this field and emphasize why elucidation of these pathways will be important for future progress in devising new and improved combinatorial therapeutic approaches for breast and other solid cancers.